Violencia obstétrica como especie de violencia de género: lineamientos teórico-conceptuales y aportes desde la responsabilidad penal en el derecho argentino - Chiosso Rapinese, Sebastián (2021)
This article deals with obstetric violence as a type of gender violence and its purpose is to highlight the magnitude and implications of a scourge that many women experience. On this premise, the main consequences associated with this type of violence against women will be identified, and experiences and testimonies will be presented to provide the empirical support on which this article is based. Against this backdrop, it will also seek to show the possible responses that the criminal legal system can provide to punish conduct in the context of obstetric violence